Altered brain functional connectivity and correlation with psychological status in patients with unilateral pulsatile tinnitus. (13th July 2019) - Xu, Yaping
Highlights: Increased ALFF was found in the left cerebellum and left ITG in PT patients by rs-fMRI. An increased FC was focused on the left cerebellum and ITG, right STG and occipital gyrus; the ITG and the thalamus in PT patients. A negative relationship was noted between the values of PSQI, SAS and FC in the ITG and the thalamus in PT patients. Abstract: The study investigated the alteration of brain functional connectivity (FC) patterns and analyzed the relationship between FC and psychological statue in pulsatile tinnitus (PT) patients by resting-state functional magnetic resonance imaging. The eligible PT patients (29) and healthy subjects (29) were enrolled. Brain activity, FC and clinical characteristics, including tinnitus handicap inventory, duration, sleep quality, anxiety, and depression were evaluated. A significantly increased brain activity in the left cerebellum and left inferior temporal gyrus was observed in PT patients. An abnormally increased FC was focused on the left cerebellum and left inferior temporal gyrus, right superior temporal gyrus, and right occipital gyrus, as well as, the inferior temporal gyrus and thalamus, the putamen and caudate nucleus. Decreased FC was demonstrated between the left cerebellum and bilateral angular gyrus, as well as, the left inferior temporal gyrus and orbital gyrus of the medial prefrontal lobe. A negative correlation was established between the scores of sleep quality and anxiety and the values of FC (in the inferior temporal gyrus and bilateral thalamus). These results suggest an abnormal activity of non-auditory cortex (the cerebellum and inferior temporal gyrus), and the alteration of FC patterns are responsible for PT. Some psychological factors may not be correlated with FC in PT patients.